The impact of the socio-educational measure for freedom assisted in the self-organization of the youth's life project in conflict with the law (Research, Society and Development, 2021)
The practice of infractions by young people is becoming more and more a public health issue, given the impact on the lives of adolescents and society in general. This research investigated the impact of the socio-educational measure of Assisted Freedom on the self-organization of the life project of adolescent authors of an infraction. This is a qualitative study, of a descriptive-exploratory nature with the collaboration of 13 adolescents, aged between 12 to 18 years old. The data were collected through a questionnaire of social and family characterization and individual interviews with semi-structured script, which were recorded and transcribed in full. The interview script covered guiding questions, which addressed the experiences of adolescents during and after the fulfillment of the socio-educational measure. The results pointed to four significant categories for young people's self-organization at the time of the measure: 1) Family and affective ties; 2) Work and study; 3) Interpersonal relationships; 4) The relationship with the Advisor. It was found, in this research, that the expanded approach of socio-educational measure as foreseen by ECA and SINASE positively impacts on the adolescent's self-organization and contributes to the structuring of the life project.